2006
DOI: 10.1158/1078-0432.ccr-05-0754
|View full text |Cite
|
Sign up to set email alerts
|

Herceptin Sensitizes ErbB2–Overexpressing Cells to Apoptosis by Reducing Antiapoptotic Mcl-1 Expression

Abstract: Purpose: Monoclonal antibodies, such as herceptin and trastuzumab, against the epidermal growth factor receptor ErbB2 (also known as HER2/neu) are an effective therapy for breast cancer patients with overexpression of ErbB2. Herceptin, in combination with standard chemotherapy, such as taxol or etoposide, gives a synergistically apoptotic response in breast tumors. Experimental Design: The mechanism underlying this synergy between chemotherapy and herceptin treatment is not well understood. Herein, we have det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 48 publications
5
57
3
Order By: Relevance
“…On the contrary, as reported earlier (Cuello et al, 2001;Valabrega et al, 2005;Henson et al, 2006;Tseng et al, 2006;Scaltriti et al, 2007), trastuzumab alone resulted in overall downregulation of HER2. As for the combined treatment with lapatinib and trastuzumab, the net result was an accumulation of receptor at the cell surface of a similar magnitude to that of lapatinib alone at each time point for MCF-7HER2 cells and starting at 36 h of treatment for SKBR-3 cells.…”
Section: Resultssupporting
confidence: 62%
“…On the contrary, as reported earlier (Cuello et al, 2001;Valabrega et al, 2005;Henson et al, 2006;Tseng et al, 2006;Scaltriti et al, 2007), trastuzumab alone resulted in overall downregulation of HER2. As for the combined treatment with lapatinib and trastuzumab, the net result was an accumulation of receptor at the cell surface of a similar magnitude to that of lapatinib alone at each time point for MCF-7HER2 cells and starting at 36 h of treatment for SKBR-3 cells.…”
Section: Resultssupporting
confidence: 62%
“…Several studies have demonstrated the ability of trastuzumab to reduce growth and induce apoptosis in HER2 pos tumors, 31 as well as to sensitize HER2 pos cells to the tumoricidal effects of cytotoxic chemotherapy. 4 Despite these benefits, the use of trastuzumab did not appreciably restore HER2-specific Th1 immunity in a majority of patients, including those with Stage I disease. In addition, an almost universal resistance to these HER2-targeted therapies is observed in advanced disease states.…”
Section: Discussionmentioning
confidence: 99%
“…2 HER2 overexpression, a molecular oncodriver in several tumor types including 20-25% of BCs, 3 is associated with an aggressive clinical course, resistance to chemotherapy, and a poor overall prognosis. 4,5 In incipient BC, HER2 overexpression is associated with enhanced invasiveness, 6 tumor cell migration, 7 and the expression of proangiogenic factors, 8 suggesting a critical role for HER2 in promoting a tumorigenic environment. Although HER2-targeted therapies (i.e., trastuzumab), in combination with chemotherapy, have significantly improved survival in HER2 pos BC, 9 a substantial proportion of patients become resistant to such therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Products of many of the anti-apoptotic YB-1 target genes have previously been implicated in drug resistance. For example, inhibition of inhibitor of apoptosis-family members cIAP1 (BIRC2) and cIAP2 (BIRC3) increases apoptosis in response to trastuzumab, lapatinib or gefitinib in HER2-overexpressing cells (Foster et al, 2009), whereas inhibition of MCL-1 sensitizes cells to both lapatinib and trastuzumab (Henson et al, 2006;Martin et al, 2008). Moreover, TNFSF18 and TCF7L1 are associated with tamoxifen and erlotinib resistance, respectively (Treeck et al, 2004;Halatsch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%